Can the digital divide be contained? - Campbell, Duncan (2001)
Summarizes the extent of the digital divide between industrialized and developing countries. Analyses the economic effects of information and communication technologies (ICTs) use. Discusses the policy fundamentals underlying the successful entry into the information economy of certain developing countries. Provides an outline of initiatives at international level to put ICTs at the service of development.